THE EFFORTS TO IMPROVE THE ACTIVITIES OF LEARNING MATHEMATICS USING COOPERATIVE LEARNING MODELS OF NHT TYPE IN SMP MUHAMMADIYAH 2 MLATI - Mayang Faulina; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning that does not involve active student participation can influence student activities, especially in mathematics learning using NHT type cooperative learning models. This study aims to determine an increase in the activity of learning mathematics in class VII D students in the even semester of SMP Muhammadiyah 2 Mlati in the 2015/2016 academic year by using the NHT type of cooperative learning model. This research is a Classroom Action Research (CAR). The setting used is class VII D, amounting to 30 students. The research plan is carried out in 3 Cycles and complete in Cycle III. In Cycle I consisted of 1 meeting, Cycle II consisted of 2 meetings, and Cycle III consisted of 1 meeting. Each Cycle uses NHT type cooperative learning models. Data collected by observation, interview and documentation. Analysis of the data used is qualitative descriptive analysis. The results showed that mathematics learning using the NHT type of cooperative learning model could increase the learning activity of students of class VII D even semester of SMP Muhammadiyah 2 Mlati, Sleman Regency Academic Year 2015/2016. This is evident from the increase in student learning activities. In Cycle I, Cycle II and Cycle III that use the NHT type of cooperative learning model experienced an increase in which the first cycle the average percentage of student activity was 37.92% with poor criteria, the average percentage of activeness in cycle II was 52.5% with sufficient criteria and the average percentage of activeness in cycle III is 65.28% with good criteria.Â